2014
DOI: 10.1155/2014/850364
|View full text |Cite
|
Sign up to set email alerts
|

Large Pyoderma Gangrenosum-Like Ulcers: A Rare Presentation of Granulomatosis with Polyangiitis

Abstract: Granulomatosis with polyangiitis (GPA), formerly known as Wegener's granulomatosis (WG), is a rare systemic vasculitis that classically manifests as necrotizing granulomas of the upper and lower respiratory tract, kidneys, and blood vessels; however, it may affect any organ system, including the skin. Cutaneous manifestations occur in up to 45% of patients during the disease course, and are the presenting feature in 9% to 14% of patients. The most common skin lesion specific to GPA is palpable purpura, with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 7 publications
1
15
0
1
Order By: Relevance
“…Other authors have reported similar findings with RTX in patients with PG or PG-like lesions who had responded unsuccessfully to corticosteroids 12,13 and immunosuppressive agents (Table 1). 1,3 In conclusion, this case shows that accurate diagnosis sometimes remains difficult, particularly in the presence of overlapping autoimmune diseases. This is when histopathological…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Other authors have reported similar findings with RTX in patients with PG or PG-like lesions who had responded unsuccessfully to corticosteroids 12,13 and immunosuppressive agents (Table 1). 1,3 In conclusion, this case shows that accurate diagnosis sometimes remains difficult, particularly in the presence of overlapping autoimmune diseases. This is when histopathological…”
Section: Discussionmentioning
confidence: 81%
“…Less frequently, articular and cutaneous involvement is seen. 1 Initially, our patient suffered polyarthritis indistinguishable from rheumatoid arthritis. However, during the course of her illness, she developed other clinical features (involvement of the respiratory tract and nervous system) that, along with positive serology tests for ANCA and anti-PR3, helped to diagnose GPA.…”
Section: Discussionmentioning
confidence: 86%
“…6 Difficulties in assessing the histopathological picture such as lack of clear diagnos� tic criteria for PG and recommendation to repeat biopsy in order to determine the proper diagnosis. 2,5,7 Therefore, epidemiological data regarding the actual co�e�istence of PG and PGA are controversial. 9,11 Genoveese et al 9 re� viewed 28 cases and established guidelines useful for dis� tinguishing these conditions: �1� typical raised, erythema� tous�wavy edges are less visible in GPA ulcers compared to PG; (2) histology of early PG lesion consists mainly of neutrophilic inflammatory infiltrate; (3) c-ANCA positiv� ity is compatible with GPA; (4) systemic involvement is common in GPA and rare in PG.…”
Section: Discussionmentioning
confidence: 99%
“…The most common skin lesions are palpable purpura, necrotic ulcera� tions, papules and nodules with many histological patterns: leukocytoclastic vasculitis, granulomatous vasculitis, and palisading granulomas. 2,3 The prevalence of GPA in Europe is 2.1-14.4 cases per million population per year. 4 Skin lesions in the course of GPA are not characteristic symptoms, but may be present in as many as 15%-50% of cases of the disease and suggest cutaneous GPA as in the case described below.…”
Section: Introductionmentioning
confidence: 99%
“…Skin involvement in GPA can manifest as PG . PG can also be triggered by trauma or surgery (pathergy) .…”
Section: Discussionmentioning
confidence: 99%